Pemodelan Ciri Getaran Teoritik dan Eksperimental Berbasis Kerja Gaya pada Mesin Reciprocating - Fransiskus Louhenapessy; Achmad Zubaydi; Suhardjono .; I Made Ariana; A.A. Masroeri (Jurnal Teknik Mesin (Sinta 3), 2010)
This study aims to model vibration response characteristics of theoretical and experimental work based force of dynamic components in reciprocating mesins. The method used was to analyze force that accumulates on main bearing area of theoretical, experimental vibration signal reconstruction and validation. Modeling involves process compression force that causes compression force and inertia force. The analysis uses a mathematical formulation of Newton are mesinered to produce a dynamic force. Results indicate that maximum total force accumulated in main bearing is 194.4 N and 29.7 N vertical direction and horizontal direction. Results of analysis theoretical and experimental vibration signals are validated by first reconstructing experimental vibration signal, in time domain and frequency to eliminate noise signals using Matlab software. Results of the validation process obtained clearance to bearing C1 = 60 μm, this value is accordance with measurement of bearing clearance dimensions manually. Modelling vibration characteristics can be used for treatment of mesin vibration signal monitoring based on scheduled.